Development and characterization of microsatellite markers in the African forest elephant (Loxodonta cyclotis). (December 2016) - Gugala, Natalie; Ishida, Yasuko; Georgiadis, Nicholas; Roca, Alfred
Abstract Background African elephants comprise two species, the savanna elephant (Loxodonta africana ) and the forest elephant (L. cyclotis ), which are distinct morphologically and genetically. Forest elephants are seriously threatened by poaching for meat and ivory, and by habitat destruction. However, microsatellite markers have thus far been developed only in African savanna elephants and Asian elephants, Elephas maximus . The application of microsatellite markers across deeply divergent lineages may produce irregular patterns such as large indels or null alleles. Thus we developed novel microsatellite markers using DNA from two African forest elephants. Findings One hundred microsatellite loci were identified in next generation shotgun sequences from two African forest elephants, of which 53 were considered suitable for testing. Twenty-three microsatellite markers successfully amplified elephant DNA without amplifying human DNA; these were further characterized in 15 individuals from Lope National Park, Gabon. Three of the markers were monomorphic and four of them carried only two alleles. The remaining sixteen polymorphic loci carried from 3 to 8 alleles, with observed heterozygosity ranging from 0.27 to 0.87, expected heterozygosity from 0.40 to 0.86, and the Shannon diversity index from 0.73 to 1.86. Linkage disequilibrium was not detected between loci, and no locus deviated from Hardy–Weinberg equilibrium. Conclusions The markers developed in this study will be useful for genetic analyses of the African forest elephant and contribute to their conservation and management.